Časná detekce sporadického karcinomu pankreatu - Frič, Přemysl; Šedo, Aleksi; Škrha, Jan; Zima, Tomáš; Bušek, Petr; Škrha, Pavel; Kmochová, Klára; Laclav, Martin; Bunganič, Bohuš; Zavoral, Miroslav (Casopis lekaru ceskych, 2016)
Pancreatic cancer (PC) behaves very differently in comparison with other malignancies. Its prevalence continuously increases, mortality does not decrease, diagnosis is frequently late, radical surgery is limited to 15-20 % of patients, postoperative relapses are frequent, and chemotherapy has a palliative character. Preventive programs are the only possibility of improvement. In familial pancreatic cancer (FPC) the knowledge of the genetic mutation enables earlier entry of specialists into the surveillance program. The repeated use of high resolution imaging methods (including endoscopy and pancreatic cytology) may be followed by more frequent detection of the precursors and earlier stages of FPC. The identification of sporadic pancreatic cancer (SPC) depends fully on the construction of a multi-step and multi-disciplinary preventive program.
Keywords: hodnocení rizik; Male; mutace; Genetic Predisposition to Disease; Risk Assessment; Risk Factors; risk factors; pancreatogenic diabetes; mužské pohlaví; Pancreatic Neoplasms; lidé; Carcinoma; risk groups.; sporadic pancreatic cancer; Humans; Early Detection of Cancer; nádory slinivky břišní; early detection; rizikové faktory; karcinom; Mutation; early symptoms; lidé středního věku; genetická predispozice k nemoci; časná detekce nádoru; Middle Aged